Mental health policies - Scheyett, Anna M. (Handbook of forensic social work, 2024)
This chapter examines policies that impact individuals with mental illness in the criminal justice system and their resultant overrepresentation and vulnerabilities. Policies are organized in two categories: in the courtroom and during incarceration. In the courtroom, the chapter reviews policies that protect the rights of individuals with mental illness including due process, competence to stand trial, and not guilty by reason of insanity. The chapter then examines policies during incarceration, including policies addressing assessment of individuals with mental illness, the right to adequate treatment while incarcerated, forced medication while incarcerated, discipline, and preparation for release from incarceration. The chapter concludes with recommendations for social workers to become educated regarding all these policies in order to advocate, both at the individual and policy levels, to protect the rights and well-being of individuals with mental illness who are involved in the criminal justice system.